Vitex rotundifolia fractions induce apoptosis in human breast cancer cell line, MCF-7, via extrinsic and intrinsic pathways - Gul-; Rehmat Jan; Habsah Mohamad; Tengku Sifzizul Tengku Muhammad (Wolters Kluwer Medknow Publications, 2019)
Breast cancer is amongst frequently diagnosed cancer type throughout the world. Due to reduced efficacy of current chemotherapeutics, several natural products have been screened for better alternatives. The cytotoxic activity of fractions prepared from leaves extract of Vitex rotundifolia (V. rotundifolia) on human breast cancer cell line, MCF-7 was studied. The fractions F1, F2, F3, and F5 of V. rotundifolia produced concentration-dependent cytotoxic effects on MCF-7 cell line. The relative potential of cytotoxicity of the fractions on MCF-7 cell line was found to be F3 > F2 > F5 > F1. The active fractions induce apoptosis in MCF-7 cell line determined by annexin V base assay. The phosphatidylserine externalization and the presence of DNA fragmentation in treated cells confirms the early and late apoptosis in treated cells. The V. rotundifolia fractions induced apoptosis by both pathways; extrinsic pathways via activation of caspase-8 and intrinsic pathways through enhanced bax/bcl-2 ratio and activation of caspase-3/7 and caspase-9 proapoptotic proteins. Furthermore, chemical profiling indicates various phenolic, flavonoids, and terpenoids compounds in the active fractions. Thus, V. rotundifolia might be a suitable candidate to investigate further and develop molecular targeted cancer therapeutics by understanding the fundamental mechanisms involved in the regulation of cell death in cancer cells.